The Healing Effects of Conditioned Medium Derived from Mesenchymal Stem Cells on Radiation-Induced Skin Wounds in Rats. Issue 1 (January 2019) - Sun, JiaYang; Zhang, YunFeng; Song, XianJi; Zhu, Jiajing; Zhu, QingSan
Radioactive dermatitis is caused by the exposure of skin and mucous membranes to radiation fields. The pathogenesis of radioactive dermatitis is complex and difficult to cure. Wharton's jelly-derived mesenchymal stem cells (WJ-MSCs) may serve as a promising candidate for the therapy of cutaneous wounds. The aim of this study was to investigate whether a WJ-MSC-derived conditioned medium (MSC-CM) could be used to treat radiation-induced skin wounds in rats using a radiation-induced cutaneous injury model. The present study was designed to examine MSC-CM therapy in the recovery of radiation-induced skin wounds in vitro and in vivo. Firstly, we prepared the MSC-CM and tested the effects of the MSC-CM on human umbilical vein endothelial cell proliferation in vitro. After that, we used a β-ray beam to make skin wounds in rats and tested the effects of MSC-CM on cutaneous wound healing in vivo. Our results indicated that MSC-CM secreted factors that promoted HUVEC proliferation, regeneration of sebaceous glands, and angiogenesis. Importantly, MSC-CM promoted wound healing in excess of the positive control (epidermal growth factor), with no, or smaller, scar formation. In conclusion, MSC-CM significantly accelerated wound closure and enhanced the wound healing quality. MSC-CM has a beneficial therapeutic effect on radiation-induced cutaneous injury skin in rats and in this way MSC-CM may serve as a basis of a novel cell-free therapeutic approach for radiation dermatitis.